Finite Element Analysis and Parameter Optimization Selection of High Speed Milling GH4169 - Geng, Guosheng; Zhang, Liang; Xiao, Maohua; Dong, Xiayun; Chen, Kailin (Manufacturing Technology Journal, 2020)
Nickel-based superalloy GH4169 has high strength and stability at high temperature and is widely used in aerospace and military fields.However, due to the problems of hard spots and poor thermal conductivity in actual processing,it is difficult for workers to select reasonable processing parameters during processing,which increases the difficulty of processing.In order to optimize the milling parameters,reduce the milling cost and operational difficulties in actual machining,we used ABAQUS finite element analysis software to simulate the 3D milling of GH4169 nickel base superalloy.The variation of milling force during milling was studied.The influences of milling speed,feed per tooth and radial depth on milling force were analyzed and the results of the simulation were compared with those obtained by orthogonal experiment.The variation of milling force was verified.Finally,we obtained the reasonable milling parameters.
Keywords: Nickel-based superalloy; ABAQUS finite element analysis; Milling force; Milling parameters